On the Functional Reinforcement of the Principle of Proportionality to Investors’ Legitimate Expectations in International Investment Arbitration - Liuhui Wang (Studies in Law and Justice, 2023)
In order to effectively balance the rights of investors with the regulatory sovereignty of host states and provide a more reasonable protection of investors’ legitimate expectations, this paper studies the strengthening effect of the proportionality principle in relation to investors’ legitimate expectations. By analyzing arbitration cases involving the principle of legitimate expectations, it becomes evident that clarifying the constitutive elements of this principle can to some extent constrain the trend towards expansive interpretations. However, with such clarification，investors’ legitimate expectations may still result in an imbalance between the regulatory authority of host states and the economic interests of investors. The proportionality principle has already been employed as an analytical framework for reconciling interests in various investment-related cases concerning legitimate expectations. Through the establishment of a rational framework for balancing interests, the proportionality principle can enhance the functionality of the principle of legitimate expectations, aligning it with the current international investment landscape.